2004
DOI: 10.1007/s00125-004-1614-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of subjects with early abnormalities of glucose tolerance in the Stockholm Diabetes Prevention Programme: the impact of sex and type 2 diabetes heredity

Abstract: Aims/hypothesis: We evaluated the impact of sex and type 2 diabetes heredity on the prevalence and pathogenesis of early abnormalities of glucose homeostasis in subjects participating in the Stockholm Diabetes Prevention Programme. Methods: A sample of 3,128 men and 4,821 women, of whom approximately half had a family history of type 2 diabetes (FHD) was categorised according to an OGTT: NGT, IFG, IGT, combined glucose intolerance and type 2 diabetes. The homeostasis model assessment was used to determine insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 30 publications
(37 reference statements)
1
48
0
1
Order By: Relevance
“…A similar pattern was seen for each group (IFG, IGT, IFG+IGT) when analysed separately. There was no significant change in fasting IGFBP-1 values in the 19 individuals with diabetes diagnosed on the basis of glucose values 2 h after oral glucose (20 μg/l [95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27] and 20 μg/l [95% CI [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] at baseline and follow up, respectively). In those who developed diabetes, fasting IGFBP-1 concentrations were higher at the 10 years followup compared with baseline (paired t tests; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar pattern was seen for each group (IFG, IGT, IFG+IGT) when analysed separately. There was no significant change in fasting IGFBP-1 values in the 19 individuals with diabetes diagnosed on the basis of glucose values 2 h after oral glucose (20 μg/l [95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27] and 20 μg/l [95% CI [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] at baseline and follow up, respectively). In those who developed diabetes, fasting IGFBP-1 concentrations were higher at the 10 years followup compared with baseline (paired t tests; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Study population The present study was an incident casecontrol study of Swedish white men who were part of a 10 year follow-up epidemiological survey, the Stockholm Diabetes Prevention Program (SDPP), which is described elsewhere [20][21][22]. The SDPP is a population-based study of individuals aged 35-56 years who were without known diabetes at the time of recruitment in 1992-1994.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, along with the increasing prevalence of obesity, the female population has been subjected to more studies. it seems that adult obese women are more insulin sensitive compared with obese adult men (Vistisen et al 2008), and the prevalence of diabetes is two to three times higher in men than in women, respective of weight categories (Kuhl et al 2005). sheep models show that restriction of fetal growth induced by chronic restriction of placental growth results in features of the metabolic syndrome in adult male offspring, particularly impaired insulin action (Owens et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that a family history of diabetes (FHD) and male sex are associated with increased prevalence of type 2 diabetes and milder forms of glucose abnormalities [7]. The aim of the present study was to further explore the influence of FHD on type 2 diabetes, separately for men and women, and with particular focus on combinations of FHD and lifestyle-related risk factors, such as obesity, physical inactivity, smoking and a low sense of coherence (SOC), which were tested for biological interaction.…”
Section: Introductionmentioning
confidence: 99%